Tele-rehabilitation for children with physical disabilities: qualitative exploration of challenges in Iran - Mahta Alsadat Aarabi; Kianoush Abdi; Farin Soleimani (BMC Pediatrics)
Abstract Background Children with physical disabilities (Having this type of disability can be due to any of the reasons such as cerebral palsy, genetic, developmental, neurodevelopment and any other reasons that cause physical disability in the child) need rehabilitation services. Tele-rehabilitation is a practical approach to provide rehabilitation services for children with rapid and continuous access. This approach has been used more recently and overcomes the limitations of conventional rehabilitation, which involves wasting time, traveling distance, and cost. The purpose of this study is to examine the challenges of telerehabilitation for children with physical disabilities such as cerebral palsy and developmental delay. Method This study was conducted with the qualitative approach of content analysis in order to investigate the challenges of tele-rehabilitation services in Tehran in 2023. Twenty-two participants were selected based on purposeful sampling with maximum variation. Data was gathered through semi-structured and in-depth interviews with children’s parents and tele-rehabilitation service providers. The interviews lasted between 15 and 75 min, and MAXQDA 10 software was used for data analysis. The conventional content analysis method of Granheim and Lundman was used to analyze the data. In this research, four Guba and Lincoln criteria including creditability, dependency, conformability, and transferability were used to evaluate the trustworthiness of data. This article is part of a more extensive qualitative study that explored the barriers and facilitators of these services. Finding For the challenges of telerehabilitation services for these children, the researcher faced with 10 categories which were obtained after the investigation. The 10 categories are as follows: unorganized internet infrastructure, lack of a developed program, inefficient technology, disregard for ethical principles, lack of therapist information, visual and auditory limitations, cultural misconceptions, weakness of empathy and therapeutic alliance, Lack of familiarity with telerehabilitation, and the other online therapy problems. Conclusion Finally, by identifying these challenges, it is possible to provide services with higher qualities to people of this group by reducing barriers. Also, the policy makers of the mentioned area should take more effective steps in order to provide this type of services to the families of children with physical disabilities, so that it ultimately leads to basic measures to improve the condition of these children.